No Limits - at Arlington, University of Texas; Open Textbook Library (Open Textbook Library, 2018)
Student Success and First Year Experience are learning community courses at UTA that teach new students academic success skills to aid their transition to college. The goal of the courses is to help students identify their individual needs, determine what resources are appropriate, recognize the faculty role in their development, and formulate a plan for an actively engaged and enriched experience from campus to career. The courses will be taught by Peer Academic Leaders (PALs) and faculty, staff and/or graduate students to provide guidance, raise awareness and understanding of students' majors and help support collaborative and co-curricular opportunities available within the School/College. This open educational resource is the required textbook for both courses.
Chapter 1: Welcome to UT Arlington -- Chapter 2: About a University -- Chapter 3: Campus Life - The value Added from Involvement -- Chapter 4: Foundations of Academic Self-Management -- Chapter 5: Self-Directed and Active Learning -- Chapter 6: Avoiding the Hazards Along the Way -- Chapter 7: Healthy Living -- Chapter 8: Self- and Career Exploration -- Chapter 9: Financial Self-Management -- Chapter 10: Campus Resources
In English.
Description based on print resource
Keywords: Academic achievement -- Textbooks